The AMPA receptor positive allosteric modulator S 47445 rescues in vivo CA3-CA1 long-term potentiation and structural synaptic changes in old mice. (1st September 2017) - Giralt, Albert; Gómez-Climent, María Ángeles; Alcalá, Rafael; Bretin, Sylvie; Bertrand, Daniel; María Delgado-García, José; Pérez-Navarro, Esther; Alberch, Jordi; Gruart, Agnès
Abstract: Positive allosteric modulators of α-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid receptors (AMPARs) are small molecules that decrease deactivation of AMPARs via an allosteric site. These molecules keep the receptor in an active state. Interestingly, this type of modulator has been proposed for treating cognitive decline in ageing, dementias, and Alzheimer's disease (AD). S 47445 (8-cyclopropyl-3-[2-(3-fluorophenyl)ethyl]-7, 8-dihydro-3H-[1, 3]oxazino[6, 5-g][1, 2, 3]benzotriazine-4, 9-dione) is a novel AMPAR positive allosteric modulator (AMPA-PAM). Here, the mechanisms by which S 47445 could improve synaptic strength and connectivity were studied and compared between young and old mice. A single oral administration of S 47445 at 10 mg/kg significantly increased long-term potentiation (LTP) in CA3-CA1 hippocampal synapses in alert young mice in comparison to control mice. Moreover, chronic treatment with S 47445 at 10 mg/kg in old alert animals significantly counteracted the deficit of LTP due to age. Accordingly, chronic treatment with S 47445 at 10 mg/kg seems to preserve synaptic cytoarchitecture in old mice as compared with young control mice. It was shown that the significant decreases in number and size of pre-synaptic buttons stained for VGlut1, and post-synaptic dendritic spines stained for spinophilin, observed in old mice were significantly prevented after chronic treatment with 10 mg/kg of S 47445. Altogether, by its different effects on LTP, VGlut1-positive particles, and spinophilin, S 47445 is able to modulate both the structure and function of hippocampal excitatory synapses known to be involved in learning and memory processes. These results open a new window for the treatment of specific age-dependent cognitive decline and dementias such as AD. Graphical abstract: Highlights: S 47445 rescues LTP deficits in hippocampal synapses of middle-aged mice. S 47445 rescues connectivity deficits in the hippocampus of middle-aged mice. S 47445 modulates both the structure and function of hippocampal excitatory synapses.